The Use of “English Tenses Practice” Application in Mobile Phone to Improve the Tenth Grade Students’ Mastery of Past Tense and Present Perfect Tense at Senior High School - Dian Pratiwi; Siti Sundari; Made Adi Andayani T. (EFL Education Journal, 2021)
This classroom action research aimed to improve the tenth grade students’ mastery of past tense and present perfect tense by using “English Tenses Practice” application and to know how the application improve the students participation during the teaching and learning process. The research participants were the X MIPA 3 students which were chosen purposively based on the students’ previous English main score. The data were collected by using grammar post-test and observation in the teaching and learning process of grammar. Then, the collected data were analyzed using descriptive statistic to know how the students’ grammar mastery and their active participation after given an action. The results of the analysis showed that the use of “English Tenses Practice” application could improve the students’ grammar mastery of past tense and present perfect tense and their participation after given an action in the first cycle. It is suggested for English teacher that “English Tenses Practice” application on mobile phone can be used as the medium in the teaching and learning process of grammar.